If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -72 = 9b Solving -72 = 9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. -72 + -9b = 9b + -9b Combine like terms: 9b + -9b = 0 -72 + -9b = 0 Add '72' to each side of the equation. -72 + 72 + -9b = 0 + 72 Combine like terms: -72 + 72 = 0 0 + -9b = 0 + 72 -9b = 0 + 72 Combine like terms: 0 + 72 = 72 -9b = 72 Divide each side by '-9'. b = -8 Simplifying b = -8
| 6x+3+1= | | 3(z-2)=(z-1) | | x-1.5=1.5 | | 5x+x+4=6x+3+1 | | -2a=(-18) | | 1/4x=100 | | 3y=(-15) | | x^6-3x^4=4x^2 | | 2x+4-3x=(-11) | | 4x-x-3=3x+2-7 | | 6x+79=10x-13 | | 6x+79=10-13 | | 2x-x-2=-x+10 | | 6+2m-2=18 | | 4sin^2(t)-14sin(t)+6=0 | | 9+10=9+x | | 6n=-3*n+45 | | 10-1(-5N+4)=-N-2(-3N+4) | | (2x+10)+79=(6x+1) | | 5x+4=91 | | 3(x-4)+2x=7x+2(x-5)-4x | | -8/-9x=24 | | -2x-1=-4x+7 | | 8(2l+9)=104 | | 5x-(7a-8b)-3x+5y-42= | | 5(X-4)-(X+1)=0 | | (5x-3)+(9+x)=180 | | 2+7x=-2+-3 | | 2/5x20/0 | | 3a+4b=36 | | 3(-4y+5)-(2y-10)= | | y+3=2x-21 |